SELF-EFFICACY IN HIGHER EDUCATION AND SATISFACTION WITH ACADEMIC EXPERIENCES. PHYSICAL EDUCATION STUDENTS' PERCEPTIONS - Oliveira, Vinicius Plentz; Porto Maciel, Larissa Fernando; Iaochite, Roberto Tadeu [UNESP]; Salles, William das Neves; Nascimento, Juarez Vieira; Folle, Alexandra (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2020)
This descriptive study analyzes the association between self-efficacy in Higher Education and Physical Education students' academic satisfaction. Participants were 251 university students enrolled in the Teacher's and Bachelor's Degrees and Physical Education at a Public University in the state of Santa Catarina, Brazil. The Higher Education Self-Efficacy Scale and the Academic Experience Satisfaction Scale were used for data collection. The data were processed using descriptive and inferential statistical resources of the SPSS software, version 25.0. The results showed mean scores above seven in all dimensions of self-efficacy, with emphasis on the social and management dimensions. Specifically, the more students perceive themselves to be effective, the more satisfied they are with the institution. The evidence underscores the importance of research focused on the relationship between academic self-efficacy and higher education students' satisfaction to improve the quality of the courses offered.
Keywords: Self Efficacy; Students; Higher Education; Physical Education